Challenges in the in vitro establishment of Guadua glomerata Munro, a bamboo native from the Amazon - Santana Rodrigues, Mateus; Lage Viana, Pedro; Moraes de Melo Souza, Joanne (Revista Multidisciplinar do Nordeste Mineiro, 2024)
This study aimed to establish in vitro protocols using nodal segments and inflorescences of Guadua glomerata, a bamboo native to the Amazon. To reduce contamination of nodal segments introduced in vitro, the culture medium was supplemented with different concentrations of the biocide PPM®. For inflorescences introduced in vitro, the surface disinfestation methodology was not effective, which made it impossible to analyze the influence of 6-Benzylaminopurine (BAP). Fungi from contaminated flasks were identified as possible fungi of the genera Trichoderma sp., Colletotrichum sp., and Arthrobotrys sp. in nodal segments introduced in vitro, while Fusarium spp. was identified in inflorescences introduced in vitro. We conclude that it is necessary to test different disinfestation methodologies for the in vitro establishment of G. glomerata. Furthermore, the identification of the fungi found in our study opens the possibility of using specific fungicides in future disinfestation attempts and thus improving the effectiveness of the process.